Manikæerne i Ægypten - Pedersen, Nils Arne (Religionsvidenskabeligt Tidsskrift, 1993)
The first part of this article contains a short overview of Manichean doctrine, ethics, history and literature in Egypt. The second part of the article deals with relations between Manichaeism and other religions in Egypt. The fundamental Manichaeism concept of other religions was that they were false, although they originally contained revelations of partial truth; their cores of truth have, however, been absorbed by Manichaeism. Furthermore, non-Manichaean religions were geographically and linguistically restricted, while Manichaeism was a universalist religion, being the final revelation of history. Consequently, the Manichees in Egypt tried to absorb previous traditions. The anti-Manichaean writing of the Neo-Platonist philosopher Alexander of Lycopolis testifies that Manichees tried to absorb pagan Hellenistic traditions in order to convert educated Greek-speaking Egyptians. The most important Manichaean mission was, however, directed towards the members of the Christian Church, and several anti-Manichaean Christians´writings from Egypt are preserved. If Ludwig Koenen's hypothesis that the "coenobitic" Christian monastery was inspired by Manichaean monasteries is accepted, the Manichees were even able to inspire their Christian competitors.